Development of lab-scale gasification systems for different possible applications - Sebe, Emese; Nagy, Gábor; Kállay, András Arnold (Analecta, 2023)
The goal of gasification is the conversion of solid fuels or carbonaceous wastes to gas that can be further used energetically or for chemically utilisation. Due to cost-effectiveness and gaining experience, the industrial application of new systems and raw materials or mixtures must be preceded by laboratory-scale experiments. The manuscript presents the laboratory scale gasification systems we designed and used, as well as the difficulties experienced during the implementation (e.g. water introduction, sealing, etc.). In addition to these, the results of one-, two- and three-stage experiments are presented as examples, where different materials such as a mixture of wood and canteen waste, brown coal and refuse derived fuel (RDF) were used for testing the system.